2013
DOI: 10.1128/ec.00160-13
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Botrytis cinerea Small GTPases BcRAS1 and BcRAC in Differentiation, Virulence, and the Cell Cycle

Abstract: bSmall GTPases of the Ras superfamily are highly conserved proteins that are involved in various cellular processes, in particular morphogenesis, differentiation, and polar growth. Here we report on the analysis of RAS1 and RAC homologues from the gray mold fungus Botrytis cinerea. We show that these small GTPases are individually necessary for polar growth, reproduction, and pathogenicity, required for cell cycle progression through mitosis (BcRAC), and may lie upstream of the stress-related mitogenactivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…By analyzing the localization of green fluorescent protein-tagged Rho4, they proved that the Rho4 had different roles in the regulation of septation during conidiation versus vegetative septation in filamentous fungi N. crassa. Recent reports showed that the Rac and Cdc42, two GTPase proteins of B. cinerea, were important for cell cycle by acting on the nuclear division (Kokkelink et al, 2011;Minz-Dub et al, 2013). The role of Rho3 in regulation of cell cycle is worthy to further study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…By analyzing the localization of green fluorescent protein-tagged Rho4, they proved that the Rho4 had different roles in the regulation of septation during conidiation versus vegetative septation in filamentous fungi N. crassa. Recent reports showed that the Rac and Cdc42, two GTPase proteins of B. cinerea, were important for cell cycle by acting on the nuclear division (Kokkelink et al, 2011;Minz-Dub et al, 2013). The role of Rho3 in regulation of cell cycle is worthy to further study.…”
Section: Discussionmentioning
confidence: 98%
“…The Rho superfamily contains three kinds of GTPase named Rac, Cdc42, and Rho, which regulate a wide spectrum of cellular functions (Kwon et al, 2011). Minz-Dub et al (2013) found that RAC protein was involved in the growth, differentiation and the virulence by regulating the actin localization and nuclear division in Botrytis cinerea. Rho3, one monomeric GTPase of the Rho superfamily, is found only in fungi.…”
Section: Introductionmentioning
confidence: 99%
“…In fungi, highly conserved members of the Rho-GTPase family, Cdc42 and Rac1, are crucial for establishing and maintaining polarity during filament formation and budding (7)(8)(9)(10). The importance of Rac homologues in comparison with Cdc42 homologues seems to increase with the developmental complexity of the fungal species (10)(11)(12)(13)(14). In C. purpurea, the two GTPases show overlapping and differing functions.…”
mentioning
confidence: 99%
“…In the gray mold, B. cinerea , bcras2 deletion leads to slowed germination and greatly reduced hyphal growth (Minz Dub et al, 2013). In spite of this, the Δ bcras2 strain is able to infect bean leaves, albeit with a delayed disease presentation.…”
Section: Plant Pathogenic Fungi: Colletotrichum Trifolii Fusariummentioning
confidence: 99%
“…It is important to note that the Ras1-like and Ras2-like homologs of filamentous fungi typically encode these differing localization motifs (Figure 2), as this dichotomy suggests the potential for differential sub-cellular localizations and, therefore, potentially unique signaling partners under physiological conditions. In support of this possibility, Ras2-like homologs have been deleted in many filamentous fungi whereas deletion of Ras1-like homologs has only been achieved for A. fumigatus , T. reesei and B. cinerea (Fortwendel et al, 2008; Minz Dub et al, 2013; Zhang et al, 2012a). The Ras1- and Ras2-like homolog paradigm is in contrast to the S. cerevisiae model, where Ras1p and Ras2p are highly homologous and have identical prenylation and palmitoylation domains, or S. pombe where only one Ras homolog exists (Weeks and Spiegelman, 2003).…”
Section: Introductionmentioning
confidence: 99%